The outcome of Pleurodesis in Malignant Pleural Effusion : No subtitle - hussen, waleed M.; H. Said, Ali; Elhassani, Osama (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Accumulation of fluid in pleural space, which is malignant in nature, is secondary to lung, breast or ovarian tumors. Metastatic Adeno Ca is most commonly seen in male and breast Ca is most commonly seen in female. It indicates advanced disease and reduced survival.Aim: Is to study prospectively thirty patients with malignant pleural effusion according to their clinical presentation, ways of diagnosis, and methods of chemical pleurodesis.Patient and methods: Data of thirty patients with malignant pleural effusion collected and analyzed using a form to categorize them according to their age, gender, presenting features, imaging studies and procedure performed to drain the fluid and to arrange chemical pleurodesis.Results: Eighteen patients were male; twelve patients were female in a ratio of 1.5:1. The youngest was 52 years old while the oldest was 81 years old. The mean age was 65.8 ±7.34. The most frequent presenting features were cough and dyspnea. Imaging studies showed that eleven patients had left sided effusion with underlying mass. Eight patients had right sided effusion with underlying mass while the remaining eleven patients had only effusion. Twenty patients received (Talc) and ten patients received (Bleomycin) with comparable recurrence rate of the  effusion, in seven patients out of 20 in Talc (35%) and in three out of 10 patients received Bleomycin (30%).Conclusion: Malignant pleural effusion should be drained nearly complete evacuation; regardless the primary cause, prior to installation of agent for pleurodesis and both (Talc & Bleomycin) can be used with comparable results and recurrence